Emotional and Neurobehavioural Status in Chronic Pain Patients - He Shuchang; He Mingwei; Jia Hongxiao; Wu Si; Yang Xing; Daniel Antonius; Mark GA Opler (Pain Research and Management)
OBJECTIVE: To investigate the emotional and neurobehavioural status of patients suffering from chronic pain.